2020
DOI: 10.3390/antibiotics9110735
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Escherichia coli Possess Elevated Growth Rates under Exposure to Sub-Inhibitory Concentrations of Azithromycin

Abstract: Antimicrobial resistance (AMR) has been identified by the World Health Organization (WHO) as one of the ten major threats to global health. Advances in technology, including whole-genome sequencing, have provided new insights into the origin and mechanisms of AMR. However, our understanding of the short-term impact of antimicrobial pressure and resistance on the physiology of bacterial populations is limited. We aimed to investigate morphological and physiological responses of clinical isolates of E. coli unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It is noteworthy that ermB containing strains had higher AZT MICs (>128 μg/ml) than majority of mphA harboring strains (MIC: 32 to >128 μg/ml), which could affect the likelihood of success of synergy with PMBN. Unfortunately, the sole effect of ermB gene could not be explored as none of the strains tested in this study possess this gene alone, which is a common limitation encountered in previous studies ( Tuan-Anh et al, 2020 ). The latter study reported that strains harboring both ermB with mphA genes had significantly higher MICs than strains without ermB gene, in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that ermB containing strains had higher AZT MICs (>128 μg/ml) than majority of mphA harboring strains (MIC: 32 to >128 μg/ml), which could affect the likelihood of success of synergy with PMBN. Unfortunately, the sole effect of ermB gene could not be explored as none of the strains tested in this study possess this gene alone, which is a common limitation encountered in previous studies ( Tuan-Anh et al, 2020 ). The latter study reported that strains harboring both ermB with mphA genes had significantly higher MICs than strains without ermB gene, in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We eliminated studies that did not perform whole-genome sequencing using Illumina platforms or did not publish raw sequencing data, leaving 3 studies for inclusion. Raw sequencing data of 751 multidrug-resistant E. coli strains previously published by Roberts et al (2022) (ENA Bioproject: PRJEB29424 and PRJEB28400), Hirabayashi et al (2021) (provided by the authors), and Tuan-Anh et al (2020) (ENA Bioproject PRJEB39354) were downloaded from the European Nucleotide Archive (ENA) database. Sixteen samples were from environmental surfaces (environmental isolates) and were collected at the National Hospital for Tropical Diseases, Hanoi, Vietnam.…”
Section: Methodsmentioning
confidence: 99%
“…One duplicate isolate (NHP1391) was excluded from the analysis. The two isolates (MH13 and MH17) from the study by Hirabayashi et al (2021) were from the Military Hospital 103 in Hanoi, and the 27 isolates from the study by Tuan-Anh et al (2020) were from the Children’s Hospital 1 in Ho Chi Minh city. Two E. coli isolates (TN1393 and XP817) were from our laboratory (NCBI SRA BioProject: PRJNA857185) and were from two patients hospitalized in the Saint Paul Hospital and the 108 Military Central Hospital, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 59 demonstrated that the previous adaptation of E. coli to formic acid also resulted in a reduction in the doubling time. Moreover, Tuan-Anh et al 60 also described an increased growth rate for pathogenic E. coli exposed to sub-inhibitory concentrations of azithromycin.…”
Section: Effect Of Ecs Exposure On a Calcoaceticus Growth Ratementioning
confidence: 99%